2011
DOI: 10.1089/dia.2010.0122
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in Peroxisome Proliferator-Activated Receptor-γ and Retinoid X Receptor-α Gene and Type 2 Diabetes Risk: A Case-Control Study of a Chinese Han Population

Abstract: The PPAR-γ and RXR-α gene variants associated with the development of T2DM in this study must be investigated in a larger population to reveal any potential effects on metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…By virtue of its role as a heterodimerization partner of other regulatory receptors involved in cell proliferation, cholesterol metabolism or insulin sensitivity as mentioned above, the effects of NR2B1 polymorphisms have mostly been investigated in relation to disease susceptibilities such as Alzheimer's disease, diabetes and various cancers to date. [31][32][33][34] For instance, IVS2¹46C>A (rs1805352) was previously identified as one of the markers within the 6-SNP haplotype significantly associated with colon cancer. 33) The remaining 5 SNPs were deep intronic SNPs which were not covered in the present study.…”
Section: A Utr and Flanking Region (Supplementarymentioning
confidence: 99%
“…By virtue of its role as a heterodimerization partner of other regulatory receptors involved in cell proliferation, cholesterol metabolism or insulin sensitivity as mentioned above, the effects of NR2B1 polymorphisms have mostly been investigated in relation to disease susceptibilities such as Alzheimer's disease, diabetes and various cancers to date. [31][32][33][34] For instance, IVS2¹46C>A (rs1805352) was previously identified as one of the markers within the 6-SNP haplotype significantly associated with colon cancer. 33) The remaining 5 SNPs were deep intronic SNPs which were not covered in the present study.…”
Section: A Utr and Flanking Region (Supplementarymentioning
confidence: 99%
“…[26] and Liu et al . [27] found that this SNP was associated with T2DM in a Chinese population. While Cho et al .…”
Section: Discussionmentioning
confidence: 99%
“…BPANN as a new approach to etiology research avoids the limitations of case control study and logistic regression without the distribution form and independence of variables. Our group has previously found the association of single nucleotide polymorphisms (SNPs) in the PPAR-γ and RXR-α genes with metabolic syndrome or type 2 diabetes risks in different populations[11],[12]. In the present study, we further explored the application characteristics of BPANN in studying the combined effects of genetic variants in the PPAR-γ and RXR-α gene and metabolic syndrome risks in a Chinese Han population.…”
Section: Introductionmentioning
confidence: 91%